Effects of Packaging and Preservation Treatments on the Shelf Life of Murtilla Fruit (Ugni Molinae Turcz) in Cold Storage - Bustos-Cerda, R (2014)
Murtilla (Ugni molinae Turcz) fruit has a unique aroma; along with its pleasant sweet flavour, this has stimulated its commercial development in international markets. This development, however, requires the application of suitable conservation methods. Five different packaging treatments for murtilla fruit (Red Pearl-INIA variety) conservation were evaluated at 0 °C for 60 days. The treatments consisted of two types of packaging [polyethylene terephthalate (PET) punnets and low-density polyethylene (LDPE) bags] and the application of an edible coating of carboxymethyl cellulose to the fruits. The incorporation of the aqueous extracts of murtilla leaves from the 18-1 and 27-1 ecotypes into the carboxymethyl cellulose edible coating was also evaluated for its antimicrobial effects. There was a significant (p < 0.05) reduction in the moisture content, a significant weight loss and an increase in soluble solids when the murtilla fruit was packed only in a PET punnet. However, with the other four treatments, in which an LDPE bag and edible coating were used, the moisture content (76.8-74.4 g/100 g) and soluble solids (15.6-17.8°Brix) in the fruit remained stable during storage. Low weight loss (1.64-2.25%) occurred in the fruits that received treatments with the LDPE bag and edible coating. Under experimental conditions and from operational facilities, packaging in PET punnets with an LDPE bag was the best alternative to preserve the murtilla fruit at 0°C for 60 days. Copyright © 2013 John Wiley & Sons, Ltd.